Development and Characterization of Ethanol-Compatibilized PPO-Based EPMM Membranes - Wang, Qiang (Université d'Ottawa / University of Ottawa, 2011)
Emulsion polymerized mixed matrix (EPMM) membranes is a new category of membranes, which incorporate silica-based inorganic nanoparticles dispersed in continuous phase of an organic polymer. The uniqueness of the EPMM membranes comes from the fact that they may combine otherwise incompatible inorganic and organic phases. This is achieved by the synthesis of the inorganic nanoparticles from a silica precursor in a stable emulsion, in which an aqueous phase is dispersed in a continuous phase of the polymer solution. More specifically, the silica precursor soluble in the polymer solution polymerizes in contact with the aqueous phase, and consequently the latter acts as finely dispersed micro reactors. The objective of this work was to optimize the previously developed protocol for the synthesis of poly (2,6-dimethyl-1,4pheneylene oxide) (PPO) based EPMM membranes, and to characterize their physical and gas transport properties. In particular, the effects of inorganic loading and the membrane post-treatment protocol on the permeability and selectivity of the membranes were of interest. However, the results showed that the obtained permeation and separation were virtually not affected by the theoretical Si loading and the post-treatment protocol. Moreover, in comparison to the base PPO membranes, the observed O2 permeability and the O2/N2 permselectivity have generally decreased. The differential scanning calorimetry (DSC) analysis of the synthesized membranes showed an important scatter of the glass transition temperatures (Tg) of the EPMM membranes with the values generally lower than the Tg of the base PPO. Moreover, the inductively coupled plasma mass spectrometry (ICP-MS) showed the silica content in selected EPMM membranes to be far below the expected theoretical level. This, in combination with the 29Si nuclear magnetic resonance (29Si NMR) results, showed that most of the already low silica content comes from the unreacted silica source (tetraethylorthosilicate) and have led to the second phase of the project in which a modified synthesis protocol has been developed. The major differences of the modified protocol compared to the original one include the replacement of a surfactant, 1-octanol, by ethanol and using greater concentrations of the reactants. To study the effect of different parameters involved in the synthesis protocol, a Gravimetric Powder experiment, in which the inorganic polymerization is carried out in an emulsion with a pure solvent rather than a polymer solution, has been designed. The Gravimetric Powder experiments have confirmed polymerization of tetraethylorthosilicate (TEOS) in the emulsion system. Using the conditions, which resulted in the maximum production of the polymerized TEOS in the Gravimetric Powder experiments, one set of new EPMM membranes has been synthesized and characterized. The new EPMM membranes have the Tg of 228.2oC, which is distinctly greater compared to the base PPO, and contain one order of magnitude more of silica compared to the old EPMM membranes. More importantly, the 29Si NMR analysis has proven that the silica content in the new EPMM membranes originates from the reacted rather than unreacted TEOS. Interestingly, the observed conversion of TEOS in the new EPMM membranes, exceeding 20%, is greater than the largest conversion in the Gravimetric Powder experiments. The oxygen permeability in the new EPMM membrane of 33.8 Barrer is more than twice that of the base PPO membrane. Moreover, this increase in O2 permeability is associated with a modest increase in the O2/N2 permselectivity (4.75 versus 4.67).
Keywords: EPMM membrane; Hybrid Material; Gas separation membrane; PPO-Based; Ethanol-Compatibilized